Prevalence of Neck Pain in Heightened Students of Rawalpindi and Islamabad - Fatima Muhammad Zahid; Humna Faheem; Umama Haq (Journal Riphah College of Rehabilitation Sciences, 2013)
Background: Neck pain is very common in Pakistani population and students are at risk neck pain because of change in life style. The aim was to determine the prevalence of neck pain in Rawalpindi and Islamabad.